DAMPAK IMPLEMENTASI QUICK RESPONSE CODE INDONESIAN STANDARD (QRIS) DALAM FUNDRAISING ZAKAT INFAQ SADAQAH (ZIS) DI BADAN AMIL ZAKAT NASIONAL (BAZNAS) KABUPATEN CIREBON PERSPEKTIF HUKUM EKONOMI SYARIAH - Mustaqim, Dede Al Mustaqim; Yasin, Ahmad Alamuddin (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
This study aims to analyze the impact of the implementation of QRIS (Quick Response Code Indonesian Standard) in collecting Zakat, Infaq, and Sadaqah (ZIS) funds at the National Amil Zakat Agency (Baznas) Cirebon Regency from the perspective of Sharia Economic Law. The development of effective digital payment methods for collecting ZIS funds is essential to ensure efficiency, fairness and security in electronic transactions. This study uses a qualitative approach by collecting data through interviews, observation, and document study. The results showed that the implementation of QRIS in ZIS fundraising at Baznas Cirebon Regency had a positive impact. QRIS speeds up the payment process, improves efficiency, and encourages wider community participation. In addition, the implementation of QRIS also supports a more equitable redistribution of wealth in society. However, there are also negative impacts that need to be considered, such as digital exclusion, privacy vulnerabilities, and risks of technology misuse. In the perspective of Sharia Economic Law, justice, redistribution of wealth, fairness in the payment mechanism, and the principles of Muamalah must be the main considerations in implementing QRIS. Based on the results of the research, it is suggested to Baznas Cirebon Regency to continue to improve community digital literacy, strengthen privacy protection and data security, and expand other payment methods to ensure inclusive access for all levels of society.